Nutrition and the gut microbiome in the elderly. (4th March 2017) - Salazar, Nuria; Valdés-Varela, Lorena; González, Sonia; Gueimonde, Miguel; de los Reyes-Gavilán, Clara G.
ABSTRACT: The gut microbiota is the assembly of microorganisms living in our intestine and their genomes are known as the microbiome. The correct composition and functionality of this microbiome is essential for maintaining a "healthy status." Aging is related to changes in the gut microbiota which are frequently associated with physiological modifications of the gastrointestinal tract, as well as, to changes in dietary patterns, together with a concomitant decline in cognitive and immune function, all together contributing to frailty. Therefore, nutritional strategies directed at restoring the microbiota in the elderly have to be addressed from a global perspective, considering not only the microbiota but also other extra-intestinal targets of action. The present review aims at summarizing the current knowledge on intestinal microbiota alterations and other functions impaired in the elderly and to analyze tools for implementing nutritional strategies, through the use of probiotics, prebiotics or specific nutrients in order to counterbalance such alterations.